Self-Regulated Learning dalam Proses Menulis Argumentatif Siswa SMA: Studi Kualitatif Deskriptif - Patricia E. P. Hurit; Rikardus Herak (Edu Berkah Khatulistiwa, 2026)
This study aims to describe senior high school students’ self-regulated learning in argumentative writing on the topic “Schools should implement a plastic-free program.” A descriptive qualitative design was employed to examine the student’s planning, strategy implementation, self-monitoring, reflection, and revision during the writing process. Data were collected through a self-regulated learning questionnaire, writing-process observation, student interview, teacher interview, reflective journal, field notes, and analysis of the written product. The data were analyzed through data reduction, thematic coding, source and technique triangulation, and interpretation based on the phases of self-regulated learning. The results show that the student demonstrated a moderately good to high tendency of self-regulated writing. The strongest indicators appeared in understanding the issue, preparing a simple outline, seeking help, accepting feedback, and rereading the text. However, several aspects still require reinforcement, particularly the use of relevant evidence, development of counterarguments, analytical monitoring of claim-reason-evidence relations, and substantive revision. The findings imply that argumentative writing instruction should integrate issue literacy, explicit argument-structure scaffolding, formative feedback, and reflective practice so that students can regulate their writing process more independently and produce stronger academic arguments.